“The Queen’s Gambit” as a Contributor to the Repositioning of Chess: What are the Marketing Implications? - Aikaterini VASSILIKOPOULOU; Irene (Eirini) KAMENIDOU; Aikaterini STAVRIANEA (Communications of International Proceedings, 2021)
"The Queen's Gambit" is a 7-episode Netflix movie that met great success Worldwide. Beth Harmon, the protagonist of the film, is a fictitious young chess player who has managed to become a chess champion despite several difficulties faced during her life. "The Queen's Gambit" stimulated significant interest in chess and a unique increase of chess fans, which also contributed to the sales increase of products and services related to chess. The current paper aims to explore the impact of the film on consumers' perceptions and attitudes towards chess, as a sport, and chess-related products and services, emphasizing marketing implications. For the purpose of the study, a questionnaire was distributed twice (i.e., before and after watching the film) to 19 consumers who were not chess players. Results demonstrated a repositioning of chess, as the pre-existed perceptions of “boring” and “it’s not for me” changed towards “interesting” and "it could be a perfect sport for me." Moreover, the purchase intentions of products (e.g., chess sets) and services (e.g., open an account in online chess platforms, arrange chess lessons) seem to experience a great increase because of the film. Based on the results, marketing implications and particular marketing communication tactics are proposed for chess clubs and relative organizations and marketers who wish to invest in a film or a film persona to influence consumers’ perceptions and promote a product or service.
Keywords: chess; “the Queen’s Gambit”; film; consumer behaviour; marketing communications